Ethyl 4-[3-(1H-imidazol-1-yl)propylamino]-3-nitrobenzoate - Yoon, Yeong Keng (International Union of Crystallography, 2011)
In the title compound, C(15)H(18)N(4)O(4), the 1H-imidazole ring forms a dihedral angle of 67.12 (8)° with the benzene ring. An S(6) ring motif is formed via an intramolecular N—H⋯O hydrogen bond. In the crystal, neighbouring molecules are linked by a pair of intermolecular N—H⋯N hydrogen bonds, forming an inversion dimer. The dimers are further linked by a pair of C—H⋯O hydrogen bonds, leading to the formation of chain along [021]. A C—H⋯π interaction involving the centroid of the benzene ring is also observed between the chains.